The Longitudinal Contribution of Early Morphological Awareness Skills to Reading Fluency and Comprehension in Greek - Manolitsis, George; Grigorakis, Ioannis; Georgiou, George K. (Frontiers in Psychology, 2017)
The purpose of this longitudinal study was to examine the role of three morphological awareness (MA) skills (inflection, derivation, and compounding) in word reading fluency and reading comprehension in a relatively transparent orthography (Greek). Two hundred and fifteen (104 girls; mean age = 67.40 months, at kindergarten) Greek children were followed from kindergarten (K) to grade 2 (G2). In K and grade 1 (G1), they were tested on measures of MA (two inflectional, two derivational, and three compounding), letter knowledge, phonological awareness, rapid automatized naming, and general cognitive ability (vocabulary and nonverbal IQ). At the end of G1 and G2, they were also tested on word reading fluency and reading comprehension. The results of hierarchical regression analyses showed that the inflectional and derivational aspects of MA in K as well as all aspects of MA in G1 accounted for 2% to 5 % of unique variance in reading comprehension. None of the morphological awareness skills predicted word reading fluency, after controlling for the effects of vocabulary and rapid automatized naming. These findings suggest that the MA skills, even when assessed as early as in kindergarten, play a significant role in reading comprehension development.